Peningkatan Proses Pembelajaran Tematik Terpadu dengan Model Problem Based Learning di Kelas V Sekolah Dasar - Putri Dwiyana Sriyati; Desyandri Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aims to describe the improvement of the integrated thematic learning process with the Problem Based Learning model in Class V SDN 14 Koto Lalang. This research is a classroom action research, using qualitative and quantitative approaches. The results showed that there was an increase in the integrated thematic learning process with the Problem Based Learning model in cycle I and cycle II. The Learning Implementation Plan (RPP) in the first cycle obtained a score of 86.11% with good qualifications (B), while the second cycle obtained a score of 100% with very good qualifications (SB). Implementation in the teacher cycle I got a score of 85.71% with good qualifications (B), while the second cycle got a score of 100% with very good qualifications (SB). Implementation in the aspect of students in cycle I obtained a score of 85.71% with good qualifications (B), while the second cycle obtained a score of 100% with very good qualifications (SB). Thus, the Problem Based Learning model can improve the learning process at SD Negeri 14 Koto Lalang.